Pengaruh Permainan Tradisional Hahayaman TerhadapPerilaku Sosial Anak Usia Dini di RA Khalifa Bojongsoang - Bahtiar, Marsya Alia Luthfiyyah Saepul; Tini, Wulan; Sahlani, Lalan (Journal of Islamic Early Childhood Education (JOIECE): PIAUD-Ku, 2025)
This study aims to analyze the effect of the traditional game Hahayaman on theb social behavior of early childhood learners in Bojongsoang Bandung. The research employed a quasi-experimental quantitative  approach using a one-group pretest–posttest design. The sampleconsisted of 44 children divided into an experimental group of 22 children and a control group of 22 children aged 5–6 years, selected through purposive sampling. The instrument used was a  social behavior observation sheet that had undergone content validity and reliability testing. The results indicate that the average social behavior score of children in the experimental group increased from 45.27 (pre-test) to 61.59 (post-test), while the control group increased from   47.77 to 57.14. Although both groups experienced improvement, the difference was not statistically significant (ρ = 0.060). The Hahayaman game demonstrated a positive impact on  children’s social behavior; however, the effect was not statistically significant. Further research  with a larger sample and more intensive intervention is needed to obtain more conclusive results.